Pre-existing immunity does not impair the engraftment of CRISPR-Cas9-edited cells in rhesus macaques conditioned with busulfan or radiation - Khaled Essawi; Waleed Hakami; Muhammad Behroz Naeem Khan; Reid Martin; Jing Zeng; Rebecca Chu; Naoya Uchida; Aylin C. Bonifacino; Allen E. Krouse; Nathaniel S. Linde; Robert E. Donahue; Gerd A. Blobel; et al. (Molecular Therapy: Methods & Clinical Development, 2023)
CRISPR-Cas9-based therapeutic genome editing approaches hold promise to cure a variety of human diseases. Recent findings demonstrate pre-existing immunity for the commonly used Cas orthologs from Streptococcus pyogenes (SpCas9) and Staphylococcus aureus (SaCas9) in humans, which threatens the success of this powerful tool in clinical use. Thus, a comprehensive investigation and potential risk assessment are required to exploit the full potential of the system. Here, we investigated existence of immunity to SpCas9 and SaCas9 in control rhesus macaques (Macaca mulatta) alongside monkeys transplanted with either lentiviral transduced or CRISPR-SpCas9 ribonucleoprotein (RNP)-edited cells. We observed significant levels of Cas9 antibodies in the peripheral blood of all transplanted and non-transplanted control animals. Transplantation of ex vivo transduced or SpCas9-mediated BCL11A enhancer-edited cells did not alter the levels of Cas9 antibodies in rhesus monkeys. Following stimulation of peripheral blood cells with SpCas9 or SaCas9, neither Cas9-specific T cells nor cytokine induction were detected. Robust and durable editing frequencies and expression of high levels of fetal hemoglobin in BCL11A enhancer-edited rhesus monkeys with no evidence of an immune response (>3 years) provide an optimistic outlook for the use of ex vivo CRISPR-SpCas9 (RNP)-edited cells.